Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/fwb.12808
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative effects matter: multi‐brood responses of Daphnia to hypoxia

Abstract: Summary Periods of hypoxia lasting up to weeks are now anticipated in fresh waters, owing to anthropogenic influences. However, the cumulative effects of hypoxia on Daphnia, over multiple broods, have received virtually no attention, and to establish and evaluate such responses there is a need to make measurements over a wide range of oxygen concentrations, potentially revealing non‐linear patterns. We predict that the effect of hypoxia on growth, survival and fecundity (i.e., production of new individuals) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…Thus, the moving of crustaceans to deep layers of the hypolimnion with low oxygen levels in natural habitats led to the depression of reproduction in terms of a high percentage of males in the population and the low egg ratio [27]. A decrease in the reproductive potential of daphnids and an increase in the period between broods with a reduction of dissolved oxygen concentration in experiments were registered earlier [28,29]. Another well-described effect of a decrease in dissolved oxygen level is body size reduction [30].…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the moving of crustaceans to deep layers of the hypolimnion with low oxygen levels in natural habitats led to the depression of reproduction in terms of a high percentage of males in the population and the low egg ratio [27]. A decrease in the reproductive potential of daphnids and an increase in the period between broods with a reduction of dissolved oxygen concentration in experiments were registered earlier [28,29]. Another well-described effect of a decrease in dissolved oxygen level is body size reduction [30].…”
Section: Discussionmentioning
confidence: 97%
“…Although reduced fish predation associated with hypoxic conditions can benefit zooplankton populations, low dissolved oxygen concentrations (<1 mg/L) have been shown to negatively impact the growth (Nebeker et al, 1992), reproduction (Hanazato et al, 1989; Lyu et al, 2016), survival (Nebeker et al, 1992) and abundance (Roman et al, 1993) of zooplankton. The mid‐summer oxygen concentrations in the hypolimnion of Lake Alvin from 2009 to 2011 were typically <0.5 mg/L, a level toxic to Daphnia spp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the transmission of phenotypes between two generations, the transmission of phenotypes in multiple broods within a generation also shows differences (Donelson et al., 2018). Studies have found that the performance of Daphnia offspring varies according to the order of brood (Lyu et al., 2016), and a study of multi‐brood offspring of rotifers also showed a similar result (Yin et al., 2015). When mothers are continuously exposed to predator kairomone for a long time, it may be reasonably speculated that, due to cumulative effects, the offspring can better inherit the mothers' phenotypes and perform stronger defences.…”
Section: Introductionmentioning
confidence: 86%